IMPLICATIONS OF PLAYING, RECREATION AND LEISURE IN THEOCCUPATIONAL THERAPEUTICAL INTERVENTION IN PEDIATRIC HOSPITAL (Fiep Bulletin - online, 2014)
In search to improve the assistance to the hospitalized child, the diverse professionals of the area of the health insert themselves in the hospital environment, each one with its uneven contribution. Between them, he has the professionals of the Occupational Therapy, which make possible a humanization's attendance hospital when longing for the quality of life translated the global promotion of the infantile development and the promotion of the health, through the integration of the child to the hospital environment, providing the involvement insignificant activities for its life, in this in case that, tricks, recreation and leisure. When looking for to erect the child world with toys, games and leisure activities, authorizes it with the possibility to transpose the limitations imposed for the illness process and hospitalization, transmitting, directly or indirectly to the health team, a perception and ampler understanding on the necessity to allow that the child is child. The present article aims to discourse on the initiatives to improve the assistance given to the hospitalized child, to explain specific on the performance of the Occupational Therapy, as well as pointing out the relevance of playing, the recreation and the leisure for the child and the context of the occupational therapeutic intervention in a children hospital environment.
Keywords: Playing; Occupational Therapy; Pediatric hospitalization